Valorization of the by-products of bluefin tuna Thunnus thynnus (Linnaeus, 1758) of the Algerian West Coast (Mostaganem): Use in Microbiology - OULHIZ, Aicha; MEZALI, Karim; SOUALILI, Dina Lila (Advances in Bioresearch, 2018)
Among seafood by-products, tuna heads represent valuable biological resources able to generate various molecules of biological and nutritional interest. The aim of this work is to highlight these by-products (head, skin, viscera, tail, etc...) in the microbiology field. The obtained results, showed that the by-products of bluefin tuna Thunnus Thynnus sampled in the west coast of Algeria has a biological value with appreciable biochemical characteristics (protein: 17%; lipids: 14.5%; Ash: 07.14%). These by-products could replace the basic elements in the preparation of microbiology medium culture and therefore bacterial growth. Through this study we conclude that these by-products form a source of bacteria of industrial interest among them we have lactic bacteria of the genus Thermobacterium.
Keywords: bluefin tuna; by-products, Microbiology, Lactic acid bacteria; West coast of Algeria